Glass kickers: training men as allies to promote women in leadership - Mattingly, Victoria Prescott, author; Kraiger, Kurt, advisor; Fisher, Gwen, committee member; Henle, Chris, committee member; Rhodes, Matthew, committee member (Colorado State University. Libraries, 2018)
Despite making up nearly half of today's workforce, women are disproportionately unrepresented in leadership roles—a phenomenon referred to as the glass ceiling. In an attempt to achieve workplace gender parity, organizations invest considerable resources in diversity and inclusion training programs. Such programs often fail to achieve intended outcomes, however, commonly placing the onus of responsibility on women themselves and neglecting to address the systemic cultural biases that perpetuate gender discrimination. With men holding the vast majority of leadership positions, they are in a position to use their power to advance women in leadership initiatives by actively supporting aspiring female leaders and serving as change agents to eradicate culturally embedded gender biases. The purpose of this research was to build and evaluate a training program that equips men to effectively serve as allies to women in the workplace. This randomly-assigned, treatment-control evaluation design used self- and other-report data to assess training effectiveness on skill-based, cognitive, and attitudinal outcomes. Data was collected from a sample of senior male leaders (n = 37) from a global manufacturing company. The results provided mixed support for increased frequency of trained ally behaviors, enhanced knowledge about workplace gender equality, and more favorable attitudes about the participants' role as allies to women in the workplace. This study provides a promising first step toward effectively inviting men into workplace gender equality initiatives, empowering them to break the glass ceiling from their position above in partnership with women trying to break it from below.
Keywords: gender equality; women in leadership; diversity training; allies; gender parity